Diving into the Digital Landscape: Assessing the Quality of Online Information on Neonatal Jaundice for Parents - Baumgartner, Michael; Behr, Anna Lena; Garbe, Anne Christina; Quatember, Christoph; Reutter, Heiko Martin; Wölfle, Joachim; Fahlbusch, Fabian Benedikt; Hanslik, Gregor (Children, 2024)
Background: Hyperbilirubinemia is a common condition in newborns. While mild cases of jaundice are common and typically resolve spontaneously, severe hyperbilirubinemia can lead to serious neurologic complications if left untreated. With the constant adaptation of guidelines, clinical management has significantly improved, and treatment has become routine for pediatricians. However, for parents of affected children, managing the condition is not routine. In today’s digital age, parents often seek additional information by accessing a wide range of medical resources on the internet. While this can be empowering, it also presents challenges, as the quality and accuracy of online medical information can vary widely. Therefore, we analyzed the current quality of information on jaundice found on the internet by parents. Methods: A simulated internet search (using the Google search engine) was conducted from a layperson’s perspective using German (“Neugeborenes Gelbsucht”, “Baby Gelbsucht”) and English (“jaundice newborn”, “jaundice baby”) search terms. Subsequently, the quality of the search results was assessed by two independent neonatologists based on the DISCERN Plus Score, HONcode certification, and the JAMA criteria. Results: Websites targeting non-medical laypersons exhibited significant variability in quality. Notably, the content of English websites was superior to that of websites in the German language. The majority of English sites were predominantly institutional, whereas most German sites were commercially oriented. Conclusions: Although information on jaundice is readily accessible online for non-medical individuals, there were notable differences in quality based on language and significant variability in the quality of information warranting attention from healthcare professionals. Furthermore, German websites providing information on jaundice were often hosted by commercial organizations. We propose that pediatric societies engage in developing and maintaining organization-based medical information to improve online resources for parents.
CRIS-Team Scopus Importer:2024-08-02
Keywords: jaundice; neonatal care; online information